(untitled) (Research, Society and Development, 2020)
The Brazilian Amazon faces a series of risks that could cause irreparable devastation even in this centenary, if limits for the management of biodiversity are not established with some urgency. These risks are mainly related to deforestation, which directly eliminates forest resources for the formation of other uses. The present work will seek to evaluate deforestation on the Boa-Vista Aerovia to Brasília, which is one of the most important roads in the Amazon region, as it refers to the connection between the capital of the northernmost state of Brazil (Amapá) and central Brazil (Distrito Federal). For the elaboration of the airway, the procedure performed was to create the shape from information on the location of the capitals (Boa Vista, Manaus and Brasília) and the trajectory of the airway. Subsequently, a 5 km radius was created using the vector geoprocessing buffer tool. For the deforestation of MapBiomas the database of increment of deforestation was extracted for the years 2008 to 2018. From the analyzed data it is identified that after 2008 there was a sharp drop in the deforestation rates that remained until 2017, the actions of control articulated with the transversal actions of several institutions such as the Prevention and Combat against Deforestation Program, may have directed this drop in rates. It is clear from the deforestation data for the period from 2008 to 2018 that the state with the largest deforested area was Pará and in second place Mato Grosso. The state with the lowest rate of deforestation was Amazonas, even though its area is much larger than that of the state of Roraima. In relation to future studies, the modeling of future scenarios for the region of the airway stands out, identifying situations of greater and less deforestation due to the presence or absence of public environmental policies.